Identification of a Non-Growth Factor Role for GM-CSF in Advanced Atherosclerosis. Issue 2 (16th January 2015) - Subramanian, Manikandan; Thorp, Edward; Tabas, Ira
<x xml:space="preserve">Abstract</x> Rationale: Granulocyte macrophage colony-stimulating factor (GM-CSF, Csf2) is a growth factor for myeloid-lineage cells that has been implicated in the pathogenesis of atherosclerosis and other chronic inflammatory diseases. However, the role of GM-CSF in advanced atherosclerotic plaque progression, the process that gives rise to clinically dangerous plaques, is unknown. Objective: To understand the role of GM-CSF in advanced atherosclerotic plaque progression. Methods and Results: Ldlr −/− mice and Csf2−/−Ldlr−/− mice were fed a Western-type diet for 12 weeks, and then parameters of advanced plaque progression in the aortic root were quantified. Lesions from the GM-CSF–deficient mice showed a substantial decrease in 2 key hallmarks of advanced atherosclerosis, lesional macrophage apoptosis and plaque necrosis, which indicates that GM-CSF promotes plaque progression. Based on a combination of in vitro and in vivo studies, we show that the mechanism involves GM-CSF–mediated production of interleukin-23, which increases apoptosis susceptibility in macrophages by promoting proteasomal degradation of the cell survival protein Bcl-2 (B-cell lymphoma 2) and by increasing oxidative stress. Conclusions: In low-density lipoprotein–driven atherosclerosis in mice, GM-CSF promotes advanced plaque progression by increasing macrophage apoptosis susceptibility. This action of GM-CSF is mediated by its interleukin-23–inducing activity rather than its role as a growth factor.